Storytelling application based on interactive story graph structure (ISGS) / Hayati Abd Rahman, Azrina Ashaari and Nur Azima Alya Narawi - Abd Rahman, Hayati; Ashaari, Azrina; Alya Narawi, Nur Azima (Universiti Teknologi MARA, 2021)
Storytelling is a process of conveying series of events and information in words, images, and sound. Conventionally, storytelling developers/writers will apply the linear narrative structure approach to deliver the stories. However, that approach has some limitations; users cannot determine the path to end the story. They have no option to choose how to end the story based on their way of storytelling. Therefore, this study is about applying an Interactive Story Graph Structure (ISGS) approach to storytelling. ISGS approach is a structure used in storytelling in which users can revert their decision when going through the storytelling application implemented during the development. After completing the storytelling prototype development, a survey was conducted to test users’ enjoyment level when using the prototype. The survey was divided into four constructs: expectation, ease of navigation, understanding, and satisfaction. There were 36 respondents, and the data were collected on a random basis. Based on the survey’s result, most users (90.28%) enjoyed the storytelling application. The storytelling prototype was developed using Adobe Animate Creative Cloud and has been distributed among the respondents randomly. The analysis was conducted to determine the findings, limitations, and recommendations for future project improvement based on the results obtained. This study’s outcome is the complete production of storytelling application, which is creative and interactive with ISGS.